Tinjauan Hukum Islam Terhadap Terjadinya Fluktuasi Harga Saham dan Pengaruh Pada Perusahaan Perbankan - Bima Pangestu (Program Pascasarjana Universitas Ibrahimy, 2021)
Islam recommended that all people work and earn a living to meet the needs of themselves and their families. Working for a living in Islam was likened to or equated with people who jihad in the way of Allah. Sharia law strongly recommends investing in halal profit. One form of investment was the sale and purchase of shares, which was a form of cooperation with other parties to obtain profits. Stocks were commodities or assets that can be traded on the stock exchange. Buying and selling shares was nothing new in this country. Transactions such as the stock exchange were regulated and the system was well organized. Buying and selling shares were one of the various types of trading transactions. Buying and selling in an Islamic economy was a business activity that can be seen in many ways, such as fiqh mu'amalah (Islamic economic law). Buying and selling securities showed that someone had ownership of the assets of a company was certainly allowed as long as it is following sharia principles, excluding elements of maysir and so on.